2023
DOI: 10.1021/acs.est.3c00182
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of FeaqII with Peroxymonosulfate and Peroxydisulfate in the Presence of Bicarbonate: Formation of FeaqIV and Carbonate Radical Anions

Abstract: Many advanced oxidation processes (AOPs) use Fenton-like reactions to degrade organic pollutants by activating peroxymonosulfate (HSO5 –, PMS) or peroxydisulfate (S2O8 2–, PDS) with Fe­(H2O)6 2+ (Feaq II). This paper presents results on the kinetics and mechanisms of reactions between Feaq II and PMS or PDS in the absence and presence of bicarbonate (HCO3 –) at different pH. In the absence of HCO3 –, Feaq IV, rather than the commonly assumed SO4 •–, is the dominant oxidizing species. Multianalytical methods ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Buffers are frequently utilized to stabilize pH levels in the exploration of catalytic oxidation mechanisms. However, these buffers could interact with the dominate oxidative species or activate the oxidants through different pathways. In addition, these buffers could alter the solubility equilibrium of metal ions in MO suspensions, which might further change the transformation pathway of DMPO. Thus, we examined the effects of different buffers, including acetate buffer solution (ABS, pH 4.00), potassium hydrogen phthalate (KHP, pH 4.01), phosphate buffer solution (PBS, pH 6.86), and borate buffer solution (BBS, pH 9.18), on the DMPO-trapping signals (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Buffers are frequently utilized to stabilize pH levels in the exploration of catalytic oxidation mechanisms. However, these buffers could interact with the dominate oxidative species or activate the oxidants through different pathways. In addition, these buffers could alter the solubility equilibrium of metal ions in MO suspensions, which might further change the transformation pathway of DMPO. Thus, we examined the effects of different buffers, including acetate buffer solution (ABS, pH 4.00), potassium hydrogen phthalate (KHP, pH 4.01), phosphate buffer solution (PBS, pH 6.86), and borate buffer solution (BBS, pH 9.18), on the DMPO-trapping signals (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly one cannot state that Fe IV (H 2 O) 5 O 2+ or Fe IV =O 2+ aq are the only form of Fe IV =O aq formed via reactions (1)–(4). The observation that Fe IV =O aq in neutral solutions reacts with DMSO & PMSO to form the corresponding sulfones [1,2,4,8,10] indicates that the alkaline forms of Fe IV =O aq react via analogous mechanisms to the reactions of Fe IV (H 2 O) 5 O 2+ with the same substrates [7] …”
Section: Discussionmentioning
confidence: 99%
“…Recently it was also shown that the reactions of Fe(H 2 O) 6 2+ with HSO 5 − or S 2 O 8 2− in neutral solutions yield Fe IV =O aq. [9,10] Due to the important role of Fe IV =O aq in AOPs, [11,12] and probably in biological processes [5,13,14] it seemed of interest to determine the reduction potential of Fe IV =O aq , and as this potential depends on the pH, pKa of the water ligands of Fe IV =O aq should be determined as well. As Fe IV =O aq is short lived, its lifetime in neutral solutions is unknown, it is difficult to determine experimentally these values.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Fe IV =O aq is expected to oxidize HCO 3 − forming CO 3 ⋅ − [39] . Furthermore, Fe IV =O aq might also be formed via the Fenton reaction in neutral media [22] .…”
Section: Figurementioning
confidence: 99%